Digitization and knowledge spillover effectiveness: Evidence from the "German Mittelstand" - Till Proeger; Petrik Runst (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
The Knowledge Spillover Theory of Entrepreneurship (KSTE) considers determinants of knowledge diffusion as well as their impact on entrepreneurial activities and growth. Extending the KSTE, the role of incumbent firms for the broad diffusion of new knowledge has been emphasized. For those firms, the barriers to an effective flow of information are considered using the concepts of knowledge filters and absorptive capacities. Both concepts enable the derivation of institutional measures to penetrate knowledge filters and systematically increase absorptive capacities. We interpret the process of digitization as a central process of knowledge spillover in recent years and determine digitization-related knowledge filters for particular domains of firm decision-making. Using a consultant-based in-depth evaluation of 200 SMEs conducted in the context of a federal innovation program, structural drivers, firm clusters and domain-specific knowledge filters for digitization are determined. We find little evidence for structural drivers of knowledge spillover effectiveness. However, as firms are clustered according to their digitization pattern, we show that firms realize high degrees of digitization in most domains or in none, leading us to argue that domain-specific knowledge filters are weak. Rather, knowledge spillover in digitization can be considered a process with initially strong general knowledge filter and - once this filter has been penetrated - weaker subsequent domain-specific knowledge filters. Policy and managerial implications for increasing digitization-related knowledge spillovers in SMEs are discussed.
Keywords: D21; D82; H41; K23; L14; 330; Digitization; Knowledge Filter; Knowledge Spillover Theory of Entrepreneurship; Small and Medium Enterprises